Penurunan Kecemasan Kehamilan melalui Kelas Prenatal - Arum Meiranny; RR Catur Leny Wulandari; Alfiah Rahmawati; Muliatul Jannah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
Anxiety is an object of uncertainty. Pregnant mothers' anxiety when facing the pregnancy process is different. Nearly 60% of pregnant women do not routinely perform ANC and most women worry about being referred to the hospital during labor, so many feel anxious. In fact, these complications can basically be detected earlier if the mother routinely and obediently performs an ANC. The solution to this problem is to reduce anxiety and optimize the motivation of pregnant women to develop a program to increase the knowledge of pregnant women and the compliance of pregnant women to carry out ANC with a discussion approach among pregnant women through the formation of Prenatal Classes. The form of science and technology transfer begins with a pre-test and ends with a post-test, education is delivered with an easy-to-understand method that provides material about: nutrition for pregnant women, discomfort of pregnant women, danger signs for pregnant women, preparation for delivery, preparation for breastfeeding, postpartum birth control, and pregnancy exercise. All participants also immediately did pregnancy exercise at the time of implementation according to instructions from the proposing team. In addition, fellow participants also discussed and exchanged experiences about their pregnancy. The anxiety level of pregnant women from the pre-test and post-test results decreased by 6.85%, participants felt calmer in dealing with the process of pregnancy, especially in the face of childbirth. The most important thing for this activity is that the mother will teach other pregnant women.